Evaluation of Incidence of Hepatitis C in Health Care Workers (Academia Journal of Medicine, 2019)
Background: Hepatitis C virus infection continues to be a major public health problem warranting high priority efforts for control and  treatment. Aim: An observational, cross-sectional facility-based study was conducted to measure the prevalence of HCV infection and to  identify risk factors associated with HCV infection among health care workers. Subjects and Methods: A total of 109 participants were  selected. It conducted through stratified random sampling. For the analysis, Z-test and Fisher’s exact test were used. All participants in this  study were tested for HCV marker (Anti-HC). Results: The positive for Anti-HC was found to be 1.8% (2/109), which was found among  nurses and paramedics. The results showed association between Anti-HC positivity and blood transfusion, frequency of blood transfusion and  exposure to sharp injuries, P values (0.003, 0.0001 and 0.029) respectively. Conclusion: Prevalence rate of Anti-HC was found to be low in  HCWs (1.8%). The prevalence rate was found among nurses and medical engineers. Blood transfusion, frequency of blood transfusion and  exposures to sharp injuries to be risk factors with Anti-HC positivity.
Keywords: HCV marker; Dialysis Centers (Units); health care workers; riskfactors; Khartoum State; Sudan